Bureau of Reclamation and the drought relief acts of 1977 and 1988 - Phillips, Tom, author; Ludwig, Jane, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
Drought conditions in widespread portions of the Western United States occurred in 1977 and again in 1987 and 1988. In each case, the Congress of the United States responded by passing legislation directing the Bureau of Reclamation to mitigate the effects of the drought through financial aid and resource management. The Drought Act of 1977 and the Reclamation States Drought Assistance Act of 1988 are essentially repetitive, differing in some implementation constraints and in some areas of emphasis. Both acts are inadequate to address the emergency nature of drought programs due to time-consuming Federal restrictions that are not waived, a lack of existing directives for implementing contingency plans, and a myriad of conflicting local, state, and Federal laws and policies. The drought crisis has passed before programs can be implemented to conserve or redistribute scarce water resources or to provide financial aid. The paper compares the two acts and provides suggestions for more appropriate legislation response for future droughts.
USCID regional meetings -- 1989
1977 and 1988 drought relief acts
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.